Respuesta :

Answer:

x+27

Step-by-step explanation:

Let's simplify step-by-step.

4(x+3)+3(5−x)

Distribute:

=(4)(x)+(4)(3)+(3)(5)+(3)(−x)

=4x+12+15+−3x

Combine Like Terms:

=4x+12+15+−3x

=(4x+−3x)+(12+15)

=x+27

Hope you find this Useful!

Answer:

x+27

Step-by-step explanation:

Distribute

4(+3)+3(5−)

4+12+3(5−)

Rearrange terms

4x+12+3(5−x)

4+12+3(−+5)

Distribute

4x+12+3(−x+5)

4+12−3+15

Add the numbers

4x+12−3x+15

4+27−3

Combine like terms

4x+27−3x

1+27

Multiply by 1

1x+27

+27